Religion in the Arab Spring: Between Two Competing Narratives. (22nd May 2014) - Hoffman, Michael; Jamal, Amaney
Abstract : Did religion promote or discourage participation in protest against authoritarian regimes during the Arab Spring? Using unique data collected in Tunisia and Egypt soon after the fall of their respective regimes, we examine how various dimensions of religiosity were associated with higher or lower levels of protest during these important events. Using these original new data, we reach a novel conclusion: Qur'an reading, not mosque attendance, is robustly associated with a considerable increase in the likelihood of participating in protest. Furthermore, this relationship is not simply a function of support for political Islam. Evidence suggests that motivation mechanisms rather than political resources are the reason behind this result. Qur'an readers are more sensitive to inequities and more supportive of democracy than are nonreaders. These findings suggest a powerful new set of mechanisms by which religion may, in fact, help to structure political protest more generally.